Estimation of Carbon Stock Storage Potential of Accacia auriculiformis dan Swietenia mahagoni (L.) in Unesa Campus Forest Area - Sari, Reyna Novita; Rachmadiarti, Fida (LenteraBio : Berkala Ilmiah Biologi, 2025)
Global climate change has triggered increased carbon emissions, threatening ecosystem balance. This research supports the campus efforts in implementing the “green campus” concept and contributes to the Sustainable Development Goals (SDGs), particulary goal 13 and 15. This research aims to analyze the relationship between morphological and physiological characteristics and carbon stock in Acacia (Acacia auriculiformis) and Mahogany (Swietenia mahagoni (L.)) in the Unesa campus forest. The method used in this research is a non-destructive approach with data collection through morphological and physiological measurements and correlation analysis using SPSS. Results showed that Mahogany has superior morphological and physiological characteristics compared to Acacia with Mahogany average height reaching 17 m and chlorophyll content of 29 mg/L. Mahogany carbon is 645 (kg C per tree per year), while Acacia is 368,43 (kg C per tree per year). There is a strong relationship between morphological and physiological characteristics and carbon stock with very strong correlations (r=0.978 to r=0.985), indicating that chlorophyll content significantly contributes to biomass accumulation and carbon. Mahogany plays an important role in climate change mitigation and should be integrated into sustainable forest management policies